The Effect of University Students’ Identity of Family Education and Virtues on the Out-Group Trust—Mediated by Cultural Self-Confidence and Moderated by Interest in the Winter Olympics - zheng, zheyun; Thirakuntham, Aphatsara (Asia Social Issues, 2023)
Following the Beijing Winter Olympics, this paper investigated 790 Chinese University students’ family education and virtues identity, cultural confidence, out-group trust, and interest in the Beijing Winter Olympics. The results of the study showed that family education and virtues identity had a positive effect on out-group trust; cultural confidence played a partial mediating role in the relationship between family education and virtues identity, and out-group trust; interest in the Winter Olympics effectively regulated the relationship between family education and virtues, cultural confidence, and out-group trust. The findings suggest that family education and virtues identity, and cultural confidence could be enhanced; further multi-disciplinary research is needed in order to provide a better understanding of the development of out-group trust and shed more light on the possible significant impact of key international events on university students.